Analisis Strategi Pemasaran Desa Wisata Senggigi (Studi Kasus Dusun Senggigi dan Dusun Loco) - Alam, Lalu Albani Panji; Permadi, Lalu Adi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The purpose of this research is to find out the marketing strategies that will be used regarding the problems faced by tourist attractions in Senggigi Hamlet and Loco Hamlet, Senggigi Tourism Village. The descriptive research method with the Mixed Methods approach is a research technique. SWOT analysis is a data analysis technique that will be applied in research. The results of the research that has been carried out have resulted in that for tourist attractions in Senggigi Hamlet and Loco Hamlet, the total Internal Factor Evaluation and External Factor Evaluation values obtained are located in quadrant I, which is profitable so that the strategy that will be implemented is a strategy that supports aggressive growth strategies. (Growth-oriented strategy). Thus, the marketing strategy focuses on improving and optimizing promotions, collaborating in managing tourist attractions with related parties, and building new tourism products that are different from other tourism.